A family of switched-impedance network enhanced-boost quasi-Z-source inverters - Vadthya Jagan; Mithun Kumar Reddy Alpuri; Mandava Neeharika; Cheruku Swetha; Pedekala Mahendar; Sharmili Das (Institute of Advanced Engineering and Science, 2022)
This paper proposes a family of novel enhanced-boost quasi-Z-source inverters (EB-qZSIs). For the similar input voltage and shoot-through duty ratio, similar to that of enhanced-boost Z-source inverter/enhanced-boost qZSIs, the presented topologies provide very high voltage boost at high modulation index with improved quality output waveform. Compared to EB-ZSI and EB-qZSIs, these topologies provide less capacitors stress, which reduce the volume and cost of the system. Akin to traditional EB-qZSIs, the presented novel impedance networks share joint ground with the source and inverter bridge, also reduces the initial inrush current. Among the four types of proposed configurations, the type-1 of discontinuous input current (DIC) EB-qZSIs offers fewer stress athwart the capacitors and little inrush current at start-up condition. Consequently, type-1 is considered and illustrated for the examination, simulation, and hardware execution. The steady-state operation and derivation of boost factor, peak direct current-link (DC-link) voltage and capacitor voltages are derived for both continuous conduction mode (CCM) and discontinuous conduction modes (DCM). The Z-network elements design, and evaluation with other Z-networks are also carried out. Lastly, the hypothetical investigation is confirmed with simulation and experimental tests.